PEMANFAATAN BERBAGAI JENIS MIKROORGANISME LOKAL (MOL) SEBAGAI BIOAKTIVATOR PADA PENGOMPOSAN SAMPAH RUMAH TANGGA - Alimuddin, Suraedah; Sabahannur, St.; Syam, Netty (Percetakan Umi Toaha Makassar, 2024)
Nationally, the highest source of waste is generated from households, namely 40.38%, while household waste is dominated by organic waste. Total waste production in Makassar City will reach 373,653.9 tons/year in 2021 or the equivalent of 0.72 kg/person/day. Efforts to overcome the high production of waste require processing waste into useful products such as compost. The addition of bioactivators such as local microorganisms can speed up the composting process. The research aimed to test various types of MOL on the quality of compost from household waste. This research was carried out using a Completely Randomized Design (CRD) with the treatment of several types of MOL, namely: tempeh MOL, rice MOL, fruit MOL, bamboo shoot MOL, and EM-4 as a comparison. The parameters observed were 1) type and density of microbes in MOL, 2) physical properties of compost: temperature, color, aroma, and texture, and 3) chemical properties of compost: levels of N, P, K, C-org, C/N, pH. The results showed that there were variations in the types of microbes in the MOL made and rice MOL had the highest microbial density, namely 8.36 x 107. Tempe MOL produced the highest compost N content (0.70%) while rice MOL produced P content (1.70% ) and K (1.84%) is the highest. Rice MOL also produces the highest N+P+K levels (3.71%) compared to other types of MOL. All types of MOL that were tried produced physical quality (color, aroma, and texture) and chemical quality of compost that met the requirements of SNI compost 19-7030-2004 except for the C-organic content of the compost